Pemanfaatan Media Powtoon Pada Materi Komik Di Sekolah Dasar - Musofa, Nafiatun; Janattaka, Nugrananda (Universitas PGRI Adi Buana Surabaya, 2019)
The purpose of this study was to describe the use of powtoon media on theme 6 the comic material class of grade V B, and describe the impact of using powtoon media on theme 6 the comic material class of grade V B. Research conducted by researchers using qualitative research methods. The researcher used a qualitative descriptive approach and the method of collecting data used observation, interviews, and documentation. This method is used to obtain data on the use of Powtoon media and the use of Powtoon media. The subjects of this study were teachers and students of the class grade V B Sumbergedong 1 Elementary School. The result showed a description of the role of powtoon media in the material comic theme 6 is teacher can use powtoon as amedium by paying attention such as making material scripts, preparing sound recordings, adding interesting image or animations, using the timeline with correctly, and saving the scene. The impact of using powtoon as about a learning can be fortered in encouraging student learning, the potential students can develop, and students can understand the steps to make comics so measily.